Influence of flooding intensity and duration on rice growth and yield - Juraimi, Abdul Shukor; Ahmad Hamdani, Muhammad Saiful; Begum, Mahfuza; Abd Rahim, Anuar; Man, Azmi (Universiti Putra Malaysia Press, 2009)
An experiment was conducted in the glasshouse of the Faculty of Agriculture, Universiti Putra Malaysia (UPM) in 2005 to evaluate the effect of different flooding treatments on rice growth and yield. Five flooding treatmentswere used, namely T1 = continuously flooded condition until maturity, T2 = early flooding until 55 DAS (day after sowing) followed by saturated condition until maturity, T3 = early flooding until 30 DAS followed by saturated condition until maturity, T4 = continuous saturated condition until maturity, T5 = continuous field capacity condition throughout the experiment period. The results showed that the response of rice plant to water soil availability varies with its growing stage. At an early stage of rice plant growth (15 and 30 DAS), flooding treatments were found to not affect the growth of rice plant significantly. However, from 45 DAS onwards, the effect was significantly pronounced. All flooding regimes (T1, T2 and T3) significantly favoured rice plant height and the number of tillers as compared to non-flooded regimes (T4 and T5). The positive correlation was observed between the grain yield and yield components. The significant higher number of tillers, high spikelets/ panicle and high 1000-grain weight had contributed to higher grain yield of rice in T1, T2 and T3 as compared to T4 and T5. Shorter duration of flooding (T2 and T3) was found to give a similar performance to continuous flooding, and thus, these methods might save on water use without reducing yields, while over watering might just increase vegetative growth.